2020
DOI: 10.3390/ijms21041366
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Transposable Elements in Immune Cells of Fibromyalgia Patients

Abstract: Advancements in nucleic acid sequencing technology combined with an unprecedented availability of metadata have revealed that 45% of the human genome constituted by transposable elements (TEs) is not only transcriptionally active but also physiologically necessary. Dysregulation of TEs, including human retroviral endogenous sequences (HERVs) has been shown to associate with several neurologic and autoimmune diseases, including Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS). However, no study has y… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 63 publications
1
23
1
Order By: Relevance
“…In chronic fatigue syndrome, differentially methylated [ 45 ] and differentially expressed genes related to the immune response [ 46 , 47 ] were identified. A recent study also showed specific transposable elements overexpressed in the immune cells of FM patients [ 48 ]. Taken as a whole, these studies, together with our finding, appear to support a possible immune system dysregulation in FM.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic fatigue syndrome, differentially methylated [ 45 ] and differentially expressed genes related to the immune response [ 46 , 47 ] were identified. A recent study also showed specific transposable elements overexpressed in the immune cells of FM patients [ 48 ]. Taken as a whole, these studies, together with our finding, appear to support a possible immune system dysregulation in FM.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond MS, temelimab seems to be effective in other HERV-W/MSRV-related diseases, such as CIDP or T1D. Therefore, it might be of interest to assess its efficacy in the treatment of additional diseases, such as fibromyalgia or chronic fatigue syndrome, where the upregulated expression of HERV-W has been recently reported [ 44 , 46 ].…”
Section: Herv-targeted Treatmentsmentioning
confidence: 99%
“…For other nervous system diseases, only a few studies have analyzed possible associations with HERV. Elevated expression of HERV has been found in progressive supranuclear palsy [ 163 ], chronic inflammatory demyelinating polyradiculoneuropathies [ 165 ], fibromyalgia [ 166 ], myalgic encephalomyelitis [ 167 , 168 , 169 ], prion disease [ 170 , 171 , 172 ], and spinal and bulbar muscular atrophy (SBMA) [ 173 ]. In the case of SBMA, HERV RNA was found unchanged but elevated levels of processed gag antigens have been found.…”
Section: Herv In Other Nervous System Disordersmentioning
confidence: 99%